ChemInform Abstract: A Bulk Boron‐Based Photocatalyst for Efficient Dechlorination: K3B6O10Br. Issue 33 (19th August 2014) - Fan, Xiaoyun; Zang, Ling; Zhang, Min; Qiu, Hengshan; Wang, Zhen; Yin, Jiao; Jia, Hanzhong; Pan, Shilie; Wang, Chuanyi
Abstract Nanoparticles of the nonlinear optical material K3B6O10Br (KBB) are fabricated by grinding of top‐seeded KBB solution‐grown single crystals.